2011
DOI: 10.4236/jbise.2011.41006
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound estimation of fetal weight in twins by artificial neural network

Abstract: This study was undertaken to determine the accuracy of using Ultrasound (US) estimation of twin fetuses by use of Artificial Neural Network. At First, as the training group, we performed US examinations on 186 healthy singleton fetuses within 3 days of delivery. Three input variables were used to construct the ANN model: abdominal circumference (AC), ab-dominal diameter (AD), biparietal diameter (BPD). Then, a total of 121 twin fetuses were assessed sub-sequently as the validation group. In validation group, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Cheng et al [ 9 ] proposed a clustering-based ANN model for birthweight prediction. Mohammadi et al [ 10 ] used an ANN to predict the weight of twin fetuses. Feng M [ 11 ] used an SVM and deep belief network (DBN) ML solution to improve the fetal weight estimation accuracy and to help the clinicians identify potential risks before delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [ 9 ] proposed a clustering-based ANN model for birthweight prediction. Mohammadi et al [ 10 ] used an ANN to predict the weight of twin fetuses. Feng M [ 11 ] used an SVM and deep belief network (DBN) ML solution to improve the fetal weight estimation accuracy and to help the clinicians identify potential risks before delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, artificial neural networks (ANN) has been applied by many researches to predict fetal weight to overcome the problems of traditional regression methods [14], [15], [16]. Comparison of estimated fetal weight (EFW) accuracy showed that these ANN models both significantly outperformed the commonly-used regression formulas.…”
Section: Introductionmentioning
confidence: 99%
“…ANNs are the computerized analog of a biological neural system and they are the important class of pattern recognizer which are useful for a wide variety of applications [14]. The architecture of the ANN model is to develop relationships between the input and output data through training on a data set [15,16]. ANNs have attracted the interest of many researches in the field of chemistry as modeling tools for multivariate calibrations [4,13,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The architecture of the ANN model is to develop relationships between the input and output data through training on a data set [15,16]. ANNs have attracted the interest of many researches in the field of chemistry as modeling tools for multivariate calibrations [4,13,[15][16][17][18][19]. Among neural networks, the most popular is the backpropagation neural network (BPNN) [4,13,17,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%